Public participation of renewable energy (Ppred) model in Malaysia: An instrument development - Abdullah W.M.Z.B.W.; Ishak W.W.B.M.; Sulong F.B.; Zia Ul Haq H.M.; Wan Nur Rahini Aznie Zainudin (Diponegoro university Indonesia - Center of Biomass and Renewable Energy (CBIORE), 2024)
Indexed by Scopus